2015
DOI: 10.1152/jn.00427.2015
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-dependent spiking relationships with the EEG

Abstract: Snyder AC, Smith MA. Stimulus-dependent spiking relationships with the EEG. J Neurophysiol 114: 1468 -1482. First published June 24, 2015 doi:10.1152/jn.00427.2015The development and refinement of noninvasive techniques for imaging neural activity is of paramount importance for human neuroscience. Currently, the most accessible and popular technique is electroencephalography (EEG). However, nearly all of what we know about the neural events that underlie EEG signals is based on inference, because of the deart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 80 publications
2
16
0
Order By: Relevance
“…Despite the widespread use of SSVEP, its precise mechanisms remain unclear, although the dominant view holds that the SSVEP results from the synchronized activity of spatially homogeneous cortical neurons in an open-field arrangement 31 . This is a simplified assumption, however, since the surface EEG can relate to the underlying neural activity in more complex ways [32][33][34][35] . Attempts to probe the nature of TF normalization at multiple scales of neural recording, therefore, could potentially shed light on the mechanisms of SSVEP generation as well.…”
mentioning
confidence: 99%
“…Despite the widespread use of SSVEP, its precise mechanisms remain unclear, although the dominant view holds that the SSVEP results from the synchronized activity of spatially homogeneous cortical neurons in an open-field arrangement 31 . This is a simplified assumption, however, since the surface EEG can relate to the underlying neural activity in more complex ways [32][33][34][35] . Attempts to probe the nature of TF normalization at multiple scales of neural recording, therefore, could potentially shed light on the mechanisms of SSVEP generation as well.…”
mentioning
confidence: 99%
“…This simple scenario was used to demonstrate the effectiveness of the procedure, in principle, and to investigate its statistical power. The assumption that two neurons have different phase modulation curves has been reported both experimentally [ 20 , 28 ] and theoretically [ 29 ]. Jia et al [ 20 ] have shown that neurons in area V1 have various preferred phases and the distribution of the preferred phase can change in response to different stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, spike trains from a pair of neural units in V4 were simultaneously recorded ( Fig 8A and 8D ) with a multi-electrode array during a fixation task in which spontaneous activity was measured. These data have been analyzed in another paper [ 28 ], which examined the relationship between individual neuron’s activity and large-scale network state. Here we wanted to test whether network-wide oscillations contribute to the excess pairwise synchrony.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations